POLISH TOURIST MARKET IN THE PERSPECTIVE OF ACTIVITIES PURSUED BYNATIONAL TOURIST ORGANIZATIONS (Research Bulletins of the Faculty of Economic Sciences, 2021)
The Polish society is becoming an increasingly more attractive segment of the ac-tivities of many tourist destinations in Europe and in the world. A growing demand for tourist services (including those abroad) on the part of Polish people also results in more active measures being taken by national tourism organizations, i.e. those entities which are responsible for the tourist promotion of a given state.The present article covers two main issues: a) Polish tourist activity for outbound tourism –primary factor which affects the interest of many NTOs, b) selected activities of European national tourism organizations that are undertaken on the Polish market (the functioning of the centers of national tourism organizations in Poland, the promo-tional activities pursued)
Keywords: tourism, organizations, Poland, promotion, activity